2008
DOI: 10.1158/0008-5472.can-07-5680
|View full text |Cite
|
Sign up to set email alerts
|

Rb Depletion Results in Deregulation of E-Cadherin and Induction of Cellular Phenotypic Changes that Are Characteristic of the Epithelial-to-Mesenchymal Transition

Abstract: The retinoblastoma tumor suppressor protein (Rb) is mutated or expressed at very low levels in several tumor types, including retinoblastoma and osteosarcoma, as well as small cell lung, colon, prostate, bladder, and breast carcinomas. Loss or reduction of Rb expression is seen most commonly in highgrade breast adenocarcinomas, suggesting that a relationship may exist between loss of Rb function and a less-differentiated state, increased proliferation, and high metastatic potential. In this study, we found tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 47 publications
7
110
1
1
Order By: Relevance
“…We found that roscovitine induced changes in the expression of proteins involved in the Rb pathway. Several changes are likely to be the result of CDK2 inhibition, including the loss of phospho-Rb and the upregulation of p53 (Arima et al, 2008). However, other observed changes in the expression of Rb pathway proteins may be independent of CDK2 inhibition, but the result from CDK7/9 inhibition, such as the loss of cyclin D1 (Aldoss et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We found that roscovitine induced changes in the expression of proteins involved in the Rb pathway. Several changes are likely to be the result of CDK2 inhibition, including the loss of phospho-Rb and the upregulation of p53 (Arima et al, 2008). However, other observed changes in the expression of Rb pathway proteins may be independent of CDK2 inhibition, but the result from CDK7/9 inhibition, such as the loss of cyclin D1 (Aldoss et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…8,39 The mechanism underlying this process remains ill-defined. Recent studies have suggested a role for the RB pathway in regulating the epithelial-to-mesenchymal transition through miR200.…”
Section: Mmac1mentioning
confidence: 99%
“…As such, we sought to determine if PIMT expression is up-regulated during the induction of EMT by TGF-β and TNF-α. Previously, treatment with a combination of TGF-β and TNF-α was shown to induce EMT in some cell types [28] . Indeed, when MDA-MB-231 breast cancer cells were treated with TGF-β/TNF-α, a morphological change from an epithelial-like to a mesenchymal-like appearance was induced ( Figure 5A).…”
Section: Knockdown Of Pimt Is Linked To the Suppression Of Emt Proteimentioning
confidence: 99%